Fundamentals of modern drafting - Wallace, Paul Ross (New Delhi : Cengage Learning Exclusive (Cbs), 2020)
This text provides a thorough introduction to contemporary drafting, covering essential technical and engineering drawing concepts and key professional applications. The author uses a highly practical, building-block approach to help you quickly develop the knowledge and skills you need to prepare working drawings for production. Coverage encompasses freehand sketching, instrument drawing, CAD, drafting conventions and formats, multiview, development, pictorial drawing procedures, geometric tolerancing practices, descriptive geometry, and more. Every chapter includes vibrant illustrations to complement the text, as well as hands-on exercises that encourage you to apply what you're learning. Now updated to reflect the latest trends and technology, this edition reflects current ASME standards to help you make a smooth transition from study and skill development to professional success.
Includes index.
Keywords: Contemporary drafting; Engineering drawing